Pengaruh Self Efficacy Terhadap Stres Akademik Mahasiswa - Ratna Trijayanti; Anis Nurul Farida (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Academic stress in students is caused by the inability to face academic challenges and demands. The level of academic stress in students can be influenced by self-efficacy. However, this is not relevant to the survey results which show that students who have low self-efficacy do not experience academic stress. The existence of this difference, then a study was conducted that aims to determine whether or not there is an influence of self-efficacy on student academic stress. The hypothesis used is that there is an influence of self-efficacy on student academic stress. This study uses quantitative methods with purposive sampling techniques. Data collection was carried out using a questionnaire and using a Likert scale. The respondents used were 45 respondents taken from Surabaya State University students in batches 2021, 2022, and 2023. This study uses inferential statistical tests, namely non-parametric statistical tests with simple regression analysis tests, and uses the help of JASP 0.18.1.0 software. The result of this study is that there is an effect of self efficacy on academic stress.